Advanced REST APIs with Flask and Python - Salvatierra, Jose (Packt Publishing, 2019)
Take your REST APIs to a whole new level with this advanced Flask and Python course! About This Video Integrate advanced functionality (such as image uploading, payments, or user confirmation e-mails) in your API Improve operations in existing REST APIs with database migrations and extensive refactoring knowledge Take your REST API development to a whole new level by getting familiar with more of the Flask ecosystem In Detail This Advanced REST API course takes your REST API development to a whole new level by familiarizing you with more of the Flask ecosystem. We start with a simple REST API and teach you everything you need to know about it. We introduce new features and technologies by baking them into this application so you can see how a professional REST API is developed. Every new feature is added to a fully working application and tested. We also help you understand more about how to build features incrementally so you can get them to your users quickly and minimize risk. Remember, this is our most advanced course yet! You should have adequate programming experience with Python or another programming language. Some knowledge of how the web works will also be helpful. You should have prior knowledge of how to install Python packages and how to run your Python applications. If you've used virtualenv or Pipenv before, that's excellent! Knowledge of how to use PyCharm for debugging is also a plus, although we cover using the debugger in the course!